1985
DOI: 10.2170/jjphysiol.35.223
|View full text |Cite
|
Sign up to set email alerts
|

Lateral spread of neuronal activity within the motor cortex investigated with intracellular responses to distant epicortical stimulation.

Abstract: 1) Lateral spread of activity within the motor cortex was examined by means of analyses of the direct cortical responses (DCRs) and intracellular responses to distant epicortical stimulation (EPICS) using cat encephale isole preparations. 2) DCRs to the EPICS at a distance of 1.5-6.5 mm consisted of initial small positive (Pd) and subsequent negative waves (Nd). The reversal of polarity in depths occurred at 400-550 µm for Pd' and at 150-250 um for Nd as well as for the initial negative wave elicited by near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…There is therefore good reason to pursue this line of comparison. More detailed analysis will be dealt with in a separate paper (EzuRE and O5HIMA, 1985b), after registering in the next paper (EZURE and OsHIMA, 1985a) the neuronal responses recorded laterally to the stimulated site on the cortex and thus summarizing the patterns of response spread in both the vertical and horizontal directions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is therefore good reason to pursue this line of comparison. More detailed analysis will be dealt with in a separate paper (EzuRE and O5HIMA, 1985b), after registering in the next paper (EZURE and OsHIMA, 1985a) the neuronal responses recorded laterally to the stimulated site on the cortex and thus summarizing the patterns of response spread in both the vertical and horizontal directions.…”
Section: Discussionmentioning
confidence: 99%
“…As has been demonstrated earlier (cf. ADRIAN, 1936;CHANG, 1951) and will be described in detail in the following paper (EZURE and OsHIMA, 1985a), a positive component wave in DCR appears earlier than DCR-N when EPICS is applied distantly more than 2 mm from the recording site. It is conceivable that some DCR-P coexists with DCR-N to near EPICS, being masked by the latter.…”
Section: Monitoring Dcr and Intensities Of Epicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although trains of stimuli, such as those used in the present study, can produce different patterns of recruitment, most penetrations from which current trains are passed yield movement of a single body part; the movement of different body parts can occur with as little as ϳ100 m displacement of electrode position. These observations would suggest that activation of distantly located output neurons by direct current spread, transynaptically, or by engaging widespread afferent or intrinsic axons is minimal (Asanuma et al, 1976;Ezure and Oshima, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, studies in cat neocortex rarely observed antidromic activation following direct cortical stimulation [74]. Moreover, the majority of responses to direct cortical stimulation propagated from superficial lamina to deep lamina [74].…”
Section: Electro-mechanistic Basis Of Cortico-cortical Evoked Potentialsmentioning
confidence: 99%